Intrathymic Plasmablasts Are Affected in Patients With Myasthenia Gravis With Active Disease. Issue 6 (November 2021) - Yamamoto, Yohei; Matsui, Naoko; Uzawa, Akiyuki; Ozawa, Yukiko; Kanai, Tetsuya; Oda, Fumiko; Kondo, Hiroyuki; Ohigashi, Izumi; Takizawa, Hiromitsu; Kondo, Kazuya; Sugano, Mikio; Kitaichi, Takashi; et al.
Abstract : Background and Objectives: To investigate intrathymic B lymphopoiesis in patients with myasthenia gravis (MG) and explore thymus pathology associated with clinical impact. Methods: Thymic lymphocytes from 15 young patients without MG, 22 adult patients without MG, 14 patients with MG without thymoma, and 11 patients with MG with thymoma were subjected to flow cytometry analysis of T follicular helper (Tfh), naive B, memory B, plasmablasts, CD19 + B220 high thymic B cells, B-cell activating factor receptor, and C-X-C chemokine receptor 5 (CXCR5). Peripheral blood mononuclear cells of 16 healthy subjects and 21 untreated patients with MG were also analyzed. Immunologic values were compared, and correlations between relevant values and clinical parameters were evaluated. Results: The frequencies of circulating and intrathymic plasmablasts were significantly higher in patients with MG than controls. On the other hand, the frequency of CD19 + B220 high thymic B cells was not increased in MG thymus. We observed a significant increase in CXCR5 expression on plasmablasts in MG thymus and an increased frequency of intrathymic plasmablasts that was correlated with preoperative disease activity. The frequency of intrathymic Tfh cells was significantly lower in patients who received immunosuppressive (IS) therapy than those without IS therapy. However, there was no significant difference in the frequency of intrathymic plasmablasts irrespective of IS therapy. Discussion: Our findings confirmed a correlation between increased frequency of intrathymic plasmablasts and disease activity before thymectomy. We postulate that activated intrathymic plasmablasts endow pathogenic capacity in MG.